Copper-based amorphous alloy toughening rejuvenation treatment method based on energy state regulation
Patent Information
- Application Number
- CN202410372195.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-03-29
AI Technical Summary
[0004]目前传统回春处理方式简单,没有考虑到能量调控对非晶合金回春的影响,不能使铜基非晶合金具有良好的韧性
1、该基于能量状态调控的铜基非晶合金增韧回春处理方法,通过调节冷热循环处理的条件,调节循环温度、调节循环间隔时间,实现铜基非晶合金回春,优化其室温压缩塑性,在保持铜基非晶合金大形成能力和优异性能的同时,提高其室温压缩、高温拉伸塑性应变能力,改善退火脆性。
Abstract
Description
Technical Field
[0001] This invention relates to the field of amorphous alloy technology, specifically to a method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation. Background Technology
[0002] When amorphous alloys undergo structural relaxation and enter a low-energy state, their strength and hardness increase, but strain localization increases, and plasticity deteriorates. JJ Lewandowski et al. used annealing to reduce the energy state of ZrTiNiCuBe amorphous alloys and found that the plastic deformation capacity of the amorphous alloys decreased significantly after annealing. Rejuvenated amorphous alloys have more free volume / rheological units, which often correspond to better plastic deformation capacity. LY Chen et al. found that CuZrAl amorphous alloys with higher cooling rates have more free volume than amorphous alloys with lower cooling rates, and their room temperature plasticity is significantly improved. WL Song et al. found that by increasing the number of thermal cycles, the defect density in the alloy gradually increases, which can gradually improve the plasticity of ZrCuAl bulk amorphous alloys. In addition, amorphous alloys usually exhibit extreme brittleness under room temperature tension, but rejuvenation treatment can improve their tensile plasticity to a certain extent. XLBian et al. found that by using high-pressure torsion, the tensile plasticity of ZrCuNiAlTi amorphous alloys increased from 0 to 0.47%. KKSong et al. also found that the tensile plasticity of cold-rolled ZrCuAl amorphous alloys increased from 0 to 0.7%. Rejuvenated alloys typically have lower shear moduli and are prone to deformation, thus their yield strength decreases. R. Raghavan et al. found that ion irradiation reduced the yield strength of ZrTiCuNiBe amorphous alloys by 30%, due to the introduction of a large amount of free volume into the alloy. Meng et al. found that after high-pressure torsion, the yield step on the load-displacement curve of the nanoindentation of ZrCuAl bulk amorphous alloys gradually decreased or even disappeared, indicating that high-pressure torsion significantly reduced the initial yield stress of the alloy. Since rejuvenation can improve the plastic deformation capacity of amorphous alloys, it can improve their fracture toughness to a certain extent. BS Li et al. found that thermal cycling can promote stable crack propagation, forming a more tortuous propagation path, significantly improving the fracture toughness of ZrCuNiAlNb amorphous alloys, up to twice that of the as-cast samples. However, the amorphous alloy with the highest energy state does not always correspond to the best plastic deformation capacity. In studies using high-pressure torsion, ion irradiation, and thermal cycling to improve the room-temperature plasticity and fracture toughness of amorphous alloys, a mismatch between energy state and plastic deformation capacity often occurs. In some cases, even improving the energy state of an amorphous alloy can worsen its plasticity and fracture toughness. W. Guo et al. obtained a rejuvenated CuZrAl amorphous alloy using thermal cycling, but its plasticity was worse than that of the relaxed state. These studies indicate that the energy state of an amorphous alloy does not perfectly correspond to its plastic deformation capacity, and the magnitude of its plasticity and toughness may be related to deeper structural factors.
[0003] Rejuvenation of amorphous alloys is typically accompanied by an increase in structural disorder, which is visually manifested as changes in density and relaxation enthalpy. When the degree of rejuvenation of an amorphous alloy is high, its free volume content is usually greater, its density is lower, and it releases more energy during relaxation during heating. High-energy X-ray diffraction can reflect the structural changes of amorphous alloys after rejuvenation. Y. Tong et al. found that the radial distribution function peak height decreased during the rejuvenation of ZrCuNiAl bulk amorphous alloy, indicating an increased degree of structural disorder. W. Dmowski et al. found that rejuvenated ZrCuAl amorphous alloys undergo large-scale atomic rearrangement and increased structural disorder. The height of the first peak of the radial distribution function decreased, and additional density was introduced on both sides, indicating the introduction of additional "free volume" and "anti-free volume" into the alloy after rejuvenation. High-resolution transmission electron microscopy can also reflect the structural changes after rejuvenation. F. Zhu et al. compared the atomic structures of amorphous alloys with the same composition in three energy states and found that high-energy amorphous alloys exhibited strong light-dark contrasts. The bright areas corresponded to a high-density matrix with numerous icosahedral-like structures, while the dark areas corresponded to a more disordered, low-density crystalline-like structure. As the energy state decreased, the diameter and number of dark areas gradually decreased, corresponding to a reduction in low-density regions, indicating that the size and volume fraction of the short / medium-range structure of the amorphous alloy were closely related to its energy state. Furthermore, the type and connection mode of the short / medium-range structure also changed significantly. S. Hilke et al. found that after deformation, the MRO of ZrCuNiAlTi amorphous alloy split into two different types compared to the as-cast state, with a smaller size and a significantly lower volume fraction, indicating a substantial increase in disorder after deformation. However, the rejuvenated state of amorphous alloys does not always correspond to a decrease in density. TPGe et al. found that after high-pressure annealing, the relaxation enthalpy of Zr-based amorphous alloys increased, indicating that the sample rejuvenated, but its density increased by 1.09%. Transmission electron microscopy results showed that the high-density region in the alloy significantly increased after high-pressure annealing. Unlike the non-uniform structure of ordinary amorphous alloys, which consist of a dense elastic matrix with loosely distributed soft regions, high-pressure annealed alloys exhibit densely packed "defect regions" within a relatively loosely arranged elastic matrix, resulting in increased density and elastic modulus. Similar changes have been observed in Ce-based amorphous alloys after high-pressure treatment. Therefore, the relationship between the energy state and structural evolution of amorphous alloys requires further clarification.
[0004] Current traditional rejuvenation methods are simple and do not take into account the impact of energy regulation on the rejuvenation of amorphous alloys, thus failing to give copper-based amorphous alloys good toughness. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation, thus solving the aforementioned problems.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation, comprising the following steps: Step 1: Sample preparation. Copper-based amorphous alloys are prepared into as-cast amorphous alloys using a vacuum casting device. Step 2: Sample cutting. The cast copper-based amorphous alloy is cut into cylindrical shapes using a cutting machine for subsequent rejuvenation treatment. Step 3: Low temperature treatment. The copper-based amorphous alloy sample is first immersed in liquid nitrogen, then taken out of the liquid nitrogen and dried with a cold air blower at room temperature. Step 4: Heat treatment. Immerse the copper-based amorphous alloy sample that was treated at low temperature in Step 3 into hot silicone oil. Then take out the copper-based amorphous alloy sample and use the residual heat of the copper-based amorphous alloy sample to evaporate the residual silicone oil on the surface. Step 5: Alternate hot and cold treatment. After completing the heat treatment in Step 4, wait 10-20 minutes before performing the low-temperature treatment in Step 3 again. At this point, one cycle is complete. Step 6: Repeat the hot and cold alternation process as in Step 5 20-30 times; Step 7: Perform structural, toughness, thermodynamic, hardness and compressive properties tests on the sample after alternating hot and cold cycles.
[0007] Preferably, in step two, water cooling is used to preserve the rejuvenated area during the cutting process, with the water temperature set at 1-4℃.
[0008] Preferably, in step three, the copper-based amorphous alloy is immersed in liquid nitrogen for 10-20 minutes.
[0009] Preferably, in step four, the temperature of the silicone oil is 513K, and the heat treatment time of the copper-based amorphous alloy is 10-20 minutes.
[0010] The copper-based amorphous alloy is composed of the following percentages of materials: 45% copper, 25% zirconium, 5% silver, 5% titanium, 3.44% nickel, 10% iron, 6.55% aluminum and 0.01% rare earth elements.
[0011] The method for preparing copper-based amorphous alloys using vacuum casting equipment is as follows: S1. Take half of copper powder, zirconium powder, silver powder, titanium powder, nickel powder, iron powder, aluminum powder and rare earth according to the proportion, and stir evenly to obtain mixed raw materials; S2. Add the mixed raw materials to the vacuum casting equipment for melting. During the melting process, place the remaining half of the material into the water-cooled copper mold crucible of the vacuum casting equipment in order of increasing element melting point. S3. Obtain a copper-based amorphous alloy with uniform composition, and repeatedly melt it 5 times. After each melting, the copper-based amorphous alloy is flipped.
[0012] Preferably, in S2, the furnace cavity is evacuated to 5×10 Pa before melting, and then filled with argon gas to 0.7 atmospheres.
[0013] Preferably, during the smelting process in S2, the titanium ingot in the furnace is first smelted for 180 seconds to remove residual oxygen from the furnace cavity.
[0014] Preferably, when S2 melts the target copper-based amorphous alloy, the copper-based amorphous alloy is held for 180 seconds after it is completely melted.
[0015] This invention provides a method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation. It has the following beneficial effects: 1. This method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation achieves the rejuvenation of copper-based amorphous alloys by adjusting the conditions of hot and cold cycling treatment, regulating the cycling temperature and the cycling interval time, optimizing their room temperature compressive plasticity, improving their room temperature compressive and high temperature tensile plastic strain capacity while maintaining the large forming capacity and excellent performance of copper-based amorphous alloys, and improving their annealing brittleness.
[0016] 2. The method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation improves the tensile properties of copper-based amorphous alloys by utilizing the structural relaxation mechanism during high-temperature tensile testing.
[0017] 3. This method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation involves adding titanium and rare earth elements to the copper-based amorphous alloy. By fine-tuning the composition, the initial energy state and atomic-scale structure of the copper-based amorphous alloy are changed, thereby improving its toughness. Furthermore, a variety of advanced characterization methods are used to explore the energy and structure that enhance the plasticity of the copper-based amorphous alloy. Detailed Implementation
[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention. Example
[0019] This invention provides a technical solution: a method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation, comprising the following steps: Step 1: Sample preparation. Copper-based amorphous alloys are prepared into as-cast amorphous alloys using a vacuum casting device. Step 2: Sample cutting. The cast copper-based amorphous alloy is cut into cylindrical shapes using a cutting machine for subsequent rejuvenation treatment. During the cutting process, water cooling is used to preserve the rejuvenated area, and the water temperature is set at 2℃. Step 3: Low-temperature treatment. The copper-based amorphous alloy sample is first immersed in liquid nitrogen, then removed from the liquid nitrogen and dried at room temperature with a cold air blower. The immersion time of the copper-based amorphous alloy in liquid nitrogen is 15 minutes. Step 4: Heat treatment. Immerse the copper-based amorphous alloy sample that underwent low-temperature treatment in Step 3 into hot silicone oil. Then, remove the copper-based amorphous alloy sample and use the residual heat of the sample to evaporate the residual silicone oil on the surface. The silicone oil temperature is 513K, and the heat treatment time for the copper-based amorphous alloy is 15 minutes. Step 5: Alternate hot and cold treatment. After completing the heat treatment in Step 4, wait 15 minutes before performing the low-temperature treatment in Step 3 again. At this point, one cycle is complete. Step Six: Repeat the hot and cold alternation process as described in Step Five 25 times; Step 7: Perform structural, toughness, thermodynamic, hardness and compressive properties tests on the sample after alternating hot and cold cycles. Example
[0020] This invention provides a technical solution for preparing copper-based amorphous alloys using vacuum casting equipment: S1. Take half of copper powder, zirconium powder, silver powder, titanium powder, nickel powder, iron powder, aluminum powder and rare earth according to the proportion, and stir evenly to obtain mixed raw materials; S2. Add the mixed raw materials to the vacuum casting equipment for melting. During the melting process, place the remaining half of the material into the water-cooled copper mold crucible of the vacuum casting equipment in order of increasing element melting point. S3. Obtain a copper-based amorphous alloy with uniform composition, and repeatedly melt it 5 times. After each melting, the copper-based amorphous alloy is flipped.
[0021] Before smelting in S2, the furnace cavity is evacuated to 5×10 Pa, and then filled with argon gas to 0.7 atmospheres.
[0022] During the S2 smelting process, the titanium ingots in the furnace are first smelted for 180 seconds to remove residual oxygen from the furnace cavity.
[0023] When S2 melts the target copper-based amorphous alloy, it is held for 180 seconds after the copper-based amorphous alloy is completely melted. Example
[0024] This invention provides a technical solution for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation, comprising the following steps: Step 1: Sample preparation. Copper-based amorphous alloys are prepared into as-cast amorphous alloys using a vacuum casting device. Step 2: Sample cutting. The cast copper-based amorphous alloy is cut into cylindrical shapes using a cutting machine for subsequent rejuvenation treatment. During the cutting process, water cooling is used to preserve the rejuvenated area, and the water temperature is set at 4℃. Step 3: Low-temperature treatment. The copper-based amorphous alloy sample is first immersed in liquid nitrogen, then removed from the liquid nitrogen and dried at room temperature with a cold air blower. The copper-based amorphous alloy is immersed in liquid nitrogen for 20 minutes. Step 4: Heat treatment. Immerse the copper-based amorphous alloy sample that underwent low-temperature treatment in Step 3 into hot silicone oil. Then, remove the copper-based amorphous alloy sample and use the residual heat of the sample to evaporate the residual silicone oil on the surface. The silicone oil temperature is 513K, and the heat treatment time for the copper-based amorphous alloy is 20 minutes. Step 5: Alternate hot and cold treatment. After completing the heat treatment in Step 4, wait 20 minutes before performing the low-temperature treatment in Step 3 again. At this point, one cycle is complete. Step Six: Repeat the hot and cold alternation process as in Step Five 30 times; Step 7: Perform structural, toughness, thermodynamic, hardness and compressive properties tests on the sample after alternating hot and cold cycles.
[0025] The copper-based amorphous alloy is composed of the following percentages of materials: 45% copper, 25% zirconium, 5% silver, 5% titanium, 3.44% nickel, 10% iron, 6.55% aluminum and 0.01% rare earth elements. Example
[0026] This invention provides a technical solution for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation, comprising the following steps: Step 1: Sample preparation. Copper-based amorphous alloys are prepared into as-cast amorphous alloys using a vacuum casting device. Step 2: Sample cutting. The cast copper-based amorphous alloy is cut into cylindrical shapes using a cutting machine for subsequent rejuvenation treatment. During the cutting process, water cooling is used to preserve the rejuvenated area, and the water temperature is set at 1℃. Step 3: Low-temperature treatment. The copper-based amorphous alloy sample is first immersed in liquid nitrogen, then removed from the liquid nitrogen and dried at room temperature with a cold air blower. The immersion time of the copper-based amorphous alloy in liquid nitrogen is 10-20 minutes. Step 4: Heat treatment. Immerse the copper-based amorphous alloy sample that underwent low-temperature treatment in Step 3 into hot silicone oil. Then, remove the copper-based amorphous alloy sample and use the residual heat of the sample to evaporate the residual silicone oil on the surface. The silicone oil temperature is 513K, and the heat treatment time for the copper-based amorphous alloy is 10 minutes. Step 5: Alternate hot and cold treatment. After completing the heat treatment in Step 4, wait 10 minutes before performing the low-temperature treatment in Step 3 again. At this point, one cycle is complete. Step Six: Repeat the hot and cold alternation process as in Step Five 20 times; Step 7: Perform structural, toughness, thermodynamic, hardness and compressive properties tests on the sample after alternating hot and cold cycles.
[0027] The copper-based amorphous alloy is composed of the following percentages of materials: 45% copper, 25% zirconium, 5% silver, 5% titanium, 3.44% nickel, 10% iron, 6.55% aluminum and 0.01% rare earth elements. Example
[0028] This invention provides a technical solution for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation, comprising the following steps: Step 1: Sample preparation. Copper-based amorphous alloys are prepared into as-cast amorphous alloys using a vacuum casting device. Step 2: Sample cutting. The cast copper-based amorphous alloy is cut into cylindrical shapes using a cutting machine for subsequent rejuvenation treatment. During the cutting process, water cooling is used to preserve the rejuvenated area, and the water temperature is set at 2℃. Step 3: Low-temperature treatment. The copper-based amorphous alloy sample is first immersed in liquid nitrogen, then removed from the liquid nitrogen and dried at room temperature with a cold air blower. The immersion time of the copper-based amorphous alloy in liquid nitrogen is 15 minutes. Step 4: Heat treatment. Immerse the copper-based amorphous alloy sample that underwent low-temperature treatment in Step 3 into hot silicone oil. Then, remove the copper-based amorphous alloy sample and use the residual heat of the sample to evaporate the residual silicone oil on the surface. The silicone oil temperature is 513K, and the heat treatment time for the copper-based amorphous alloy is 15 minutes. Step 5: Alternate hot and cold treatment. After completing the heat treatment in Step 4, wait 15 minutes before performing the low-temperature treatment in Step 3 again. At this point, one cycle is complete. Step Six: Repeat the hot and cold alternation process as described in Step Five 25 times; Step 7: Perform structural, toughness, thermodynamic, hardness and compressive properties tests on the sample after alternating hot and cold cycles.
[0029] The copper-based amorphous alloy is composed of the following percentages of materials: 45% copper, 25% zirconium, 5% silver, 5% titanium, 3.44% nickel, 10% iron, 6.55% aluminum and 0.01% rare earth elements.
[0030] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, the phrase "comprising an element defined as..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0031] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation, characterized in that, It consists of the following steps: Step 1: Sample preparation. Copper-based amorphous alloys are prepared into as-cast amorphous alloys using a vacuum casting device. Step 2: Sample cutting. The cast copper-based amorphous alloy is cut into cylindrical shapes using a cutting machine for subsequent rejuvenation treatment. Step 3: Low temperature treatment. The copper-based amorphous alloy sample is first immersed in liquid nitrogen, then taken out of the liquid nitrogen and dried with a cold air blower at room temperature. Step 4: Heat treatment. Immerse the copper-based amorphous alloy sample that was treated at low temperature in Step 3 into hot silicone oil. Then take out the copper-based amorphous alloy sample and use the residual heat of the copper-based amorphous alloy sample to evaporate the residual silicone oil on the surface. Step 5: Alternate hot and cold treatment. After completing the heat treatment in Step 4, wait 10-20 minutes before performing the low-temperature treatment in Step 3 again. At this point, one cycle is complete. Step 6: Repeat the hot and cold alternation process as in Step 5 20-30 times; Step 7: Perform structural, toughness, thermodynamic, hardness and compressive properties tests on the samples after alternating hot and cold cycles; In step two, water cooling is used to preserve the rejuvenated area during the cutting process, with the water temperature set at 1-4℃; In step three, the copper-based amorphous alloy is immersed in liquid nitrogen for 10-20 minutes. In step four, the silicone oil temperature is 513K, and the heat treatment time for the copper-based amorphous alloy is 10-20 minutes. The copper-based amorphous alloy is composed of the following 100% materials: 45% copper, 25% zirconium, 5% silver, 5% titanium, 3.44% nickel, 10% iron, 6.55% aluminum and 0.01% rare earth elements.
2. The method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation according to claim 1, characterized in that, The method for preparing copper-based amorphous alloys using vacuum casting equipment in step one is as follows: S1. Take half of copper powder, zirconium powder, silver powder, titanium powder, nickel powder, iron powder, aluminum powder and rare earth according to the proportion, and stir evenly to obtain mixed raw materials; S2. Add the mixed raw materials to the vacuum casting equipment for melting. During the melting process, place the remaining half of the material into the water-cooled copper mold crucible of the vacuum casting equipment in order of increasing element melting point. S3. Obtain a copper-based amorphous alloy with uniform composition, and repeatedly melt it 5 times. After each melting, the copper-based amorphous alloy is flipped.
3. The method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation according to claim 2, characterized in that: Before smelting in S2, the furnace cavity is evacuated to 5×10 Pa, and then filled with argon gas to 0.7 atmospheres.
4. The method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation according to claim 2, characterized in that: During the S2 smelting process, the titanium ingots in the furnace are first smelted for 180 seconds to remove residual oxygen from the furnace cavity.
5. The method for toughening and rejuvenating copper-based amorphous alloys based on energy state regulation according to claim 2, characterized in that: When S2 melts the target copper-based amorphous alloy, it is held for 180 seconds after the copper-based amorphous alloy is completely melted.
Citation Information
Patent Citations
Method for improving amorphous alloy plasticity through low-temperature thermal circulation
CN109972065A
Method for simultaneously improving yield strength and plasticity of bulk amorphous alloy composite material
CN115807199A